Studi Kasus Perencanaan Pembelajaran Kewirausahaan Berbasis Teknologi di SMAN 2 Purwokerto - Andry Reva Raja Saputra; Lalita Melasarianti; Nia Ulfa Martha (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
In the current era, technology assists human roles in life. The important role of technology leads humanity toward an unlimited modern world. Moreover, technology is present to facilitate and support the world of education. This includes engaging learning videos, the presence of e-books (digital books) and e-modules (digital modules), and the emergence of interactive applications. The presence of increasingly advanced technological innovations in learning will facilitate both students and teachers. Supported by digital learning resources, students become more creative and active during learning, and adequate facilities make technology-based learning enjoyable, with students accepting it wholeheartedly. One example is at SMA Negeri 2 Purwokerto, where the facilities already meet general standards and certainly address students' needs. This research uses a qualitative method with a case study approach. The population used is from classes XII-1 to XII-11, while the sample only includes class XII-1, with data collection encompassing observation, documentation, and interviews. The research results reveal that in designing learning planning, there must be a clear flow, such as the creation of learning achievements, teaching modules, and strategic steps in learning. This is to create interactive and engaging learning. In addition, it can make learning more organized, especially entrepreneurship education at SMAN 2 Purwokerto.